Safety issues of robotics in an automated manufacturing system - Bhuvenesh, Rajamony, Prof. Dr. (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organised by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM) and Prince of Songkla University (PSU), Thailand, 14th - 15th May 2005 at Putra Palace Hotel, Kangar, Perlis.